Genome-Wide Investigation of Hsf Genes in Sesame Reveals Their Segmental Duplication Expansion and Their Active Role in Drought Stress Response - Dossa, Komivi; Diouf, Diaga; Cissé, Ndiaga (Frontiers in Plant Science, 2016)
Sesame is a survivor crop cultivated for ages in arid areas under high temperatures and limited water conditions. Since its entire genome has been sequenced, revealing evolution and functional characterization of its abiotic stress genes became a hot topic. In this study, we performed a whole-genome identification and analysis of Hsf gene family in sesame. Thirty genes encoding Hsf domain were found and classified into 3 major classes A, B and C. The class A members were the most representative one and Hsf genes were distributed in 12 of the 16 linkage groups (except the LG 8, 9, 13 and 16). Evolutionary analysis revealed that, segmental duplication events which occurred around 67 MYA, were the primary force underlying Hsf genes expansion in sesame. Comparative analysis also suggested that sesame has retained most of its Hsf genes while its relatives viz. tomato and potato underwent extensive gene losses during evolution. Continuous purifying selection has played a key role in the maintenance of Hsf genes in sesame. Expression analysis of the Hsf genes in sesame revealed their putative involvement in multiple tissue-/developmental stages. Time-course expression profiling of Hsf genes in response to drought stress showed that 90% Hsfs are drought responsive. We infer that classes B-Hsfs might be the primary regulators of drought response in sesame by cooperating with some class A genes. This is the first insight into this gene family and the results provide some gene resources for future gene cloning and functional studies towards the improvement in stress tolerance of sesame.